2009
DOI: 10.1016/j.jada.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Parental Feeding Practices in the United States and in France: Relationships with Child's Characteristics and Parent's Eating Behavior

Abstract: word count: 226Text word count: 1866 words plus abstract (226 words) and references (536 words) Abstract Given the role of parental feeding practices in establishing children's eating habits, understanding sources of individual differences in feeding practices is important. This study examined the role of several psychological variables (i.e., parental perceived responsibility for child's eating, parental perceptions of the child's weight, and parents' own eating patterns) in individual differences in a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 21 publications
8
71
2
1
Order By: Relevance
“…Based on existing literature responsibility [13,14] and monitoring [6,13,14,15] were positively weighted, with pressure to eat [7,8,9,10,11] and restriction [18] negatively weighted by adding one to maximum scores, and then subtracting the domain score. For example, a PTE score of 4 would have become (6 − 4) = 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on existing literature responsibility [13,14] and monitoring [6,13,14,15] were positively weighted, with pressure to eat [7,8,9,10,11] and restriction [18] negatively weighted by adding one to maximum scores, and then subtracting the domain score. For example, a PTE score of 4 would have become (6 − 4) = 2.…”
Section: Methodsmentioning
confidence: 99%
“…Parental responsibility for child dietary intake [13,14] and monitoring of consumption, particularly in relation to discretionary foods [6,13,14,15] have been consistently associated with healthy eating behaviours and weight status in children. However, the measurement of some child feeding practices can be challenging due to the complexity of concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that emotional eating in adolescents is affected by family environment, including parental eating habits as well as parenting and feeding practices (de Lauzon-Guillain, Musher-Eizenman, Leporc, Holub, & Charles, 2009;Faith, Scanlon, Birch, Francis, & Sherry, 2004;Topham et al, 2011) and personal factors, including stress level, stress coping styles, and personality (Elfhag & Morey, 2008;Larsen, van Strien, Eisenga, & Engels, 2006;Wallis & Hetherington, 2004). Few studies have examined possible mediators of the relationship between negative emotions and emotional eating.…”
Section: Introductionmentioning
confidence: 99%
“…This study determined that emotional feeding is the third most influential factor in female adolescent obesity. In the literature, parents with emotional feeding habits give more food to their children when they or their children are under stress [14,36,37]. It has been argued that this also increases junk food consumption [37,14].…”
Section: Ss Altan and M Bektasmentioning
confidence: 99%
“…In the literature, parents with emotional feeding habits give more food to their children when they or their children are under stress [14,36,37]. It has been argued that this also increases junk food consumption [37,14]. On the other hand, parents with the tendency to eat less when they are under emotional stress may give less food to their children when they or their children are under stress [35].…”
Section: Ss Altan and M Bektasmentioning
confidence: 99%